Internet of Things on Banking Processes in South Africa: A Systematic Reflection on Innovations, Opportunities and Challenges - Paul Kariuki; Lizzy Oluwatoyin Ofusori; Maria Lauda Joel Goyayi (Digital Business)
The Internet of Things (IoT) represents a digital revolution that is defining global connections across sectors and people at a rapid pace. This extension of the internet beyond the electronic world transforms sectors and industries irrespective of their locality and core business. At the root of this revolution is the desire to improve the delivery of goods and services efficiently and effectively through the digital interconnection of people, places, and physical things. This qualitative study aimed to examine IoT's influence on banking processes in South Africa. The study utilized a systematic review of the literature to collect its data. The researchers preferred a systematic approach because they were interested in gaining insight into the topic from the existing body of literature about IoT and its use by the banking sector. The study found that while the use of IoT in banking processes is still in its infancy, most banks have enhanced their customer experiences through IoT innovations, enhanced their security systems, and enhanced their data access ecosystem to improve their operational efficiency.Moreover, the banking sector is still experiencing some challenges regarding the use of IoT in its processes, such as a lack of privacy and proper storage of customer information, limited workflow management processes, and a lack of policy framework to guide the sector as far as adoption of IoT is concerned. The study recommends that the banking sector fast-track the development of a policy framework to guide its use and adoption of IoT and its processes to enhance client experiences and better workflow management while minimizing the risks associated with the protection of client information. The South African banking ecosystem should embrace a culture of continuous innovation and adaptation to keep pace with evolving customer expectations and corresponding digital trends.